Exhibition by boys from Woodville Gardens combined cycle speed way at McLaren Vale, South Australia, 18 June, 1957 (1957)
"Boys from the Woodville Gardens Combined Cycle Speedway at a picnic at McLaren Vale yesterday, gave an exhibition of cycling on a track at the rear of a garage. One of the young riders comes to grief when he slides on the loose surface"--Part of newspaper article glued on verso.
Title devised by cataloguer based on information from verso.
Condition: Yellowing, discoloration and creases.
Inscriptions: "Cycle smash"--In pencil upper right.
Also available online
Keywords: Bicycle racing -- South Australia -- McLaren Vale -- Photographs; McLaren Vale (S.A.) -- Photographs